Fostering teacher educators' professional development in research and in supervising student teachers' research. Issue 8 (16th November 2016) - Geerdink, Gerda; Boei, Fer; Willemse, Martijn; Kools, Quinta; Van Vlokhoven, Haske
Abstract: Most teacher educators who work at institutes for higher vocational education have faced a new role since the European Community aimed to upgrade the general quality of education. Research tasks have been added as a new important core business for institutes that used to be mainly focused on education. Teacher educators therefore have to become familiar with research knowledge and skills, and with the skills to supervise student teachers in conducting research. Professional development activities have been set up to prepare them for it. In this explorative study, we investigated the extent to which four different professional development activities within three Dutch institutes for teacher education contributed to the knowledge and skills needed for these new tasks. We gathered data by interviewing 12 teacher educators. In addition to some striking differences, we found corresponding positive experiences in all four activities. Exchanging experiences and discussing issues with colleagues was perceived to be the most outstanding part of each activity. This research has yielded necessary insights into constructing professional development activities. It is clear that any professional development activity about research should be consistent with teacher educators' daily practices and concerns.